An Irreversible Inhibitor of HSP72 that Unexpectedly Targets Lysine‐56. (22nd February 2017) - Pettinger, Jonathan; Le Bihan, Yann‐Vaï; Widya, Marcella; van Montfort, Rob L. M.; Jones, Keith; Cheeseman, Matthew D.
Abstract: The stress‐inducible molecular chaperone, HSP72, is an important therapeutic target in oncology, but inhibiting this protein with small molecules has proven particularly challenging. Validating HSP72 inhibitors in cells is difficult owing to competition with the high affinity and abundance of its endogenous nucleotide substrates. We hypothesized this could be overcome using a cysteine‐targeted irreversible inhibitor. Using rational design, we adapted a validated 8‐ N ‐benzyladenosine ligand for covalent bond formation and confirmed targeted irreversible inhibition. However, no cysteine in the protein was modified; instead, we demonstrate that lysine‐56 is the key nucleophilic residue. Targeting this lysine could lead to a new design paradigm for HSP72 chemical probes and drugs. Abstract : Irreversibel : Das stressinduzierbare molekulare Chaperon HSP72 ist ein wichtiger onkologischer Angriffspunkt, doch nur wenige Inhibitoren konnten validiert werden. Ein durch rationales Design entdeckter irreversibler Nucleotid‐kompetitiver Inhibitor, der unerwartet an Lysin 56 angreift, kann die hohe Affinität und Häufigkeit der endogenen Substrate von HSP72 überwinden.